Pengaruh Persepsi Resiko dan Persepsi Kemudahan Penggunaan Terhadap Minat Beli Online di E-Commerce Lazada Dengan Kepercayaan Konsumen Sebagai Variabel Intervening - Jelsa Maisela; Annur Fitri Hayati (Universitas Negeri Padang, 2025)
This study aimed to understand the impact of perceived risk and ease of use on purchase intention, as well as to evaluate consumer confidence as an intervening variable. The population in this study, which is causal, are students at Universitas Negeri Padang who have used the Lazada e-commerce platform (not necessarily made purchases). Using the Cochran formula and purposive sampling method, the number of samples is calculated to be as high as 100. The information utilized is a kind of primary data collected via questionnaires. Using SmartPLS 4. 0 software, SEM analysis is the technique used in the study. The study's findings show that: 1) risk perception has no bearing on purchase intent; 2) perceived ease of use has little bearing on purchase intent; 3) risk perception has little bearing on trust; 4)has a major influence on the perceived simplicity of use consumer trust; 5) consumer trust has a significant impact on purchase intention; 6)the link between risk perception and purchase intention cannot be mediated by consumer trust; and 7) The connection between perceived ease of use and purchase intent is mediated by consumer trust.